Pengaruh Pemberian Media Pop-Up Book Terhadap Tingkat Pengetahuan Keamanan Pangan pada Jajanan Anak Sekolah di SDN LIK Layana Indah - Fangki Heriyanto; Nurdiana Nurdiana; Adillah Imansari (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
The impact of consuming unhealthy snacks can cause foodborne disease. The purpose of this study was to analyze the effect of nutrition education through pop-up book media on the level of knowledge of food safety in school snacks at Inpres LIK Layana Indah State Elementary School. The research design used was a quasi experimental pre-test and post-test with a population of 30 students in grade 5 and grade 6. The instruments used were Pop-up book media and questionnaires. Data were analyzed using data normality test, homogeneity test and hypothesis testing. The results of the study obtained abnormal data in the experimental class (p-value = 0.001) and abnormal control (p-value = 0.006), there was a significant effect between the experimental and control groups on increasing student knowledge related to snack safety (p-value = 0.001). There is no significant difference between the control group with powerpoint media and the experimental class with pop-uo book media based on a significant value> 0.05.